The Influence of Perceived Ease of Use and Perceived Usefulness on Repurchase Intention with Customer Satisfaction as a Mediating Variable - Luthfyyah, Salma; Istanti, Fredianaika (Universitas Syiah Kuala, 2025)
In this study, the impact of perceived ease of use and usefulness on repurchase intention is examined using customer satisfaction as a mediating variable for Tokopedia users in Tangerang Regency. Using a quantitative approach with a qualitative approach, 107 respondents were selected using the purposive sample technique. The Partial Least SquareStructural Equation Model (PLS-SEM) method is used for data analysis. The study's findings indicate that perceived ease of use has a positive and significant impact on repurchase intention on customer satisfaction.Conversely, Perceived usefulness has no impact on repurchase intention; it simply influences customer satisfaction. Furthermore, the association between perceived ease of use and usefulness and repurchase intention has not been shown to be mediated by customer satisfaction. According to this research, perceived utility is insufficient to motivate repurchase decisions in the absence of customer happiness, while simplicity of use is a significant element in fostering customer loyalty. The findings of this study suggest that e-commerce managers should concentrate more on creating user-friendly systems in order to boost client loyalty and happiness